Group Classification of Generalized Eikonal Equations - Egorchenko, I. A.; Popovich, R. O. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
By using a new approach to a group classification, we perform a symmetry analysis of equations of the form u a u a = F(t, u, u t) that generalize the well-known eikonal and Hamilton–Jacobi equations.